Can a heterogeneous gastronomic environment reduce food neophobia? It depends on political orientation. (February 2023) - Guidetti, Margherita; Ferretti, Fabrizio; Cavazza, Nicoletta
Highlights: Contextual factors can reduce food neophobia. Food neophobia decreased with gastronomic heterogeneity in the neighborhood. For liberals, neophobia decreased with heterogeneity in both neighborhood and city. These data help explain the association between place of residence and neophobia. Abstract: This paper reports an empirical study investigating the negative relationship between the perceived exposure of individuals to a heterogeneous gastronomic environment and their level of food neophobia, over and above the known individual antecedents. In addition, considering the social roots of food neophobia, we tested whether participants' political orientation moderated this relationship. Our results confirmed these hypotheses: liberals' food neophobia decreased with increasing gastronomic heterogeneity, but this was not true for conservatives. The implications of these findings are important in both theory and practice as they highlight a contextual factor that may reduce food neophobia, an individual orientation that has a negative impact on both health and the environment.